2019
DOI: 10.3390/s19194286
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Kinematic-Acoustic System for Automated Activity Detection of Construction Equipment

Abstract: Automatically recognizing and tracking construction equipment activities is the first step towards performance monitoring of a job site. Recognizing equipment activities helps construction managers to detect the equipment downtime/idle time in a real-time framework, estimate the productivity rate of each equipment based on its progress, and efficiently evaluate the cycle time of each activity. Thus, it leads to project cost reduction and time schedule improvement. Previous studies on this topic have been based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 66 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…2) SPECTRAL FLUX Spectral flux (SF) [44] measures the rate with which the power spectrum of a signal changes. The power spectrum from one window has been compared with the power spectrum from a preceding window of the signal.…”
Section: Figure 5 Renyi Entropy For Standing Sitting Picking Up An Ob...mentioning
confidence: 99%
“…2) SPECTRAL FLUX Spectral flux (SF) [44] measures the rate with which the power spectrum of a signal changes. The power spectrum from one window has been compared with the power spectrum from a preceding window of the signal.…”
Section: Figure 5 Renyi Entropy For Standing Sitting Picking Up An Ob...mentioning
confidence: 99%
“…However, recently diverse studies investigated and showed the potentials of audiobased construction site monitoring, which can be a promising method for advanced unmanned field monitoring (Sherafat et al, 2020(Sherafat et al, , 2019. It has been found that this new approach can obtain satisfactory performance and reliability (Cho et al, 2017;Sharan & Moir, 2016;Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [ 10 ] proposed a sensor fusion method by configuring both kinematic and audio signals that permits the classification of the construction equipment’s activities.…”
Section: Introductionmentioning
confidence: 99%